Pemberdayaan Perempuan Melalui Pengembangan Ekonomi Berbasis Pariwisata Studi Kasus Waduk Gajah Mungkur - Raihan Cris Setyo Ardi; Aisyah, Siti (eScience Humanity Journal, 2024)
A problem often faced by developing countries is the high income inequality among the population. On the other hand, women's empowerment as part of the development strategy has been developed in various literatures and concepts of thought, although its implementation has not been maximized. This study aims to determine the effect of women's empowerment through tourism-based economic development in Gajah Mungkur Reservoir, Wonogiri, Indonesia. This research uses a mixed method that combines qualitative and quantitative approaches. The research sample was taken by purposive sampling from 50 women MSME players who are active in tourism activities at Gajah Mungkur Reservoir. Data were obtained through in-depth interviews and the Resident Empowerment through Tourism Scale (RETS) with the addition of economic dimensions. The results showed that women's involvement in the tourism sector had a positive impact on increasing income and economic independence. In addition, participation in tourism activities strengthens women's social and political position in the community and increases their confidence and pride in environmental preservation and local cultural heritage.